2021
DOI: 10.3390/ijms222312773
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Capture Investigation in Plasma-Activated Water and Its Antifungal Effect on Cryptococcus pseudolongus Cells

Abstract: This research investigated the capture of nitrate by magnesium ions in plasma-activated water (PAW) and its antifungal effect on the cell viability of the newly emerged mushroom pathogen Cryptococcus pseudolongus. Optical emission spectra of the plasma jet exhibited several emission bands attributable to plasma-generated reactive oxygen and nitrogen species. The plasma was injected directly into deionized water (DW) with and without an immersed magnesium block. Plasma treatment of DW produced acidic PAW. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 54 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…At the plasma–liquid interface, prolonged plasma exposure causes a dissociation of water molecules by energetic ions from the plasma jet, resulting in radical generation. Weak emission bands in the 330−380 nm range are generated from the second positive system transition of nitrogen molecules ( ) [ 37 , 38 ], which can be ascribed to plasma operation under atmospheric conditions. The emission at 777 nm was attributed to transition of atomic oxygen ( O ) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the plasma–liquid interface, prolonged plasma exposure causes a dissociation of water molecules by energetic ions from the plasma jet, resulting in radical generation. Weak emission bands in the 330−380 nm range are generated from the second positive system transition of nitrogen molecules ( ) [ 37 , 38 ], which can be ascribed to plasma operation under atmospheric conditions. The emission at 777 nm was attributed to transition of atomic oxygen ( O ) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The investigation focused on nitrate capture in PAW, and its antifungal effect on Cryptococcus pseudolongus cells was observed in [137]. The study found that enriching PAW with magnesium ions (PAW-Mg 2+ ) resulted in the control of free nitrate through the formation of nitrate salts by magnesium ions.…”
Section: Atmospheric Pressure Plasma Jets and Plasma Torchmentioning
confidence: 99%
“…PTW has been shown to have antifungal effects on various fungal pathogens, but its effect on the newly emerged mushroom pathogen Cryptococcus pseudolongus is unknown. Lee et al investigated the capture of nitrate by magnesium ions in PTW and its antifungal effect on C. pseudolongus [6]. The plasma jet generated several reactive oxygen and nitrogen species, and plasma treatment of deionized water produced acidic PTW.…”
Section: Effect On Environmentally Transmitted Pathogens and Biofilmsmentioning
confidence: 99%